Changes in Myocardial Composition and Conduction Properties in Rat Heart Failure Model Induced by Chronic Volume Overload - Sedmera, David; Neckar, Jan; Benes, Jiri; Pospisilova, Jana; Petrak, Jiri; Sedlacek, Kamil; Melenovsky, Vojtech (Frontiers in Physiology, 2016)
Volume overload leads to development of eccentric cardiac hypertrophy and heart failure. In our previous report, we have shown myocyte hypertrophy with no fibrosis and decrease in gap junctional coupling via connexin43 in a rat model of aorto-caval fistula at 21 weeks. Here we set to analyze the electrophysiological and protein expression changes in the left ventricle and correlate them with phenotypic severity based upon ventricles to body weight ratio. ECG analysis showed increased amplitude and duration of the P wave, prolongation of PR and QRS interval, ST segment elevation and decreased T wave amplitude in the fistula group. Optical mapping showed a prolongation of action potential duration in the hypertrophied hearts. Minimal conduction velocity (CV) showed a bell-shaped curve, with a significant increase in the mild cases and there was a negative correlation of both minimal and maximal CV with heart to body weight ratio. Since the CV is influenced by gap junctional coupling as well as the autonomic nervous system, we measured the amounts of tyrosine hydroxylase (TH) and choline acetyl transferase (ChAT) as a proxy for sympathetic and parasympathetic innervation, respectively. At the protein level, we confirmed a significant decrease in total and phosphorylated connexin43 that was proportional to the level of hypertrophy, and similarly decreased levels of TH and ChAT. Even at a single time-point, severity of morphological phenotype correlates with progression of molecular and electrophysiological changes, with the most hypertrophied hearts showing the most severe changes that might be related to arrhythmogenesis.